2004
DOI: 10.1653/0015-4040(2004)087[0152:dagvor]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Genetic Variation of Reticulitermes(isoptera: Rhinotermitidae) in Oklahoma

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…The closest records are from the Delta of Mississippi and South Carolina forests where R. flavipes and R. virginicus are the predominant species (Gentry andWhitford 1982, Howard et al 1982), unlike Missouri where R. hageni and R. flavipes dominate woodlands. R. hageni and R. virginicus were found more frequently in woody areas than in urban areas and this agrees with observations from states where these species are more common in undisturbed habitats or areas where forests are prevalent (Gentry and Whitford 1982, Howard et al 1982, Austin et al 2004a.…”
Section: R Flavipessupporting
confidence: 89%
See 3 more Smart Citations
“…The closest records are from the Delta of Mississippi and South Carolina forests where R. flavipes and R. virginicus are the predominant species (Gentry andWhitford 1982, Howard et al 1982), unlike Missouri where R. hageni and R. flavipes dominate woodlands. R. hageni and R. virginicus were found more frequently in woody areas than in urban areas and this agrees with observations from states where these species are more common in undisturbed habitats or areas where forests are prevalent (Gentry and Whitford 1982, Howard et al 1982, Austin et al 2004a.…”
Section: R Flavipessupporting
confidence: 89%
“…In our study, we found the same two haplotypes occurring in woodland and urban environments, which are also two of the three R. hageni haplotypes recorded from North America. Haplotype RHM2 from Missouri is equivalent with haplotype H1 and haplotype RHM3 is equivalent with H2, whereas no equivalent was found in Missouri for H3 (Austin et al 2004a).…”
Section: R Flavipesmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, it can be assumed that the present distribution of Reticulitermes populations in Portugal is mainly the result of the natural population dynamics without an overall anthropogenic effect. As an example of the opposite situation, Austin et al (2004) found, in Oklahoma, an important anthropogenic role in the distribution pattern of populations as indicated by the absence of geographic association of the haplotypes.…”
Section: Discussionmentioning
confidence: 99%